Pengaruh Integritas, Kompetensi, Independensi, dan Motivasi Terhadap Kualitas Audit Aparat Inspektorat dalam Pengawasan Keuangan Daerah (Studi Kasus Pada Inspektorat Pemerintahan Kota Pangkalpinang) - Arpian Arpian; Rulyanti Susi Wardhani (Journal of Accountancy, 2013)
Influence of Integrity, Competence, Independence and Motivation Of the Quality of Audit in Financial Supervision Inspectorate Apparatus Area (a Case Study on Government Inspectorate Pangkalpinang city). The aim of this research is to find out the influence of integrity, competence, independence, and motivation of the quality of Audit in Financial Supervision Inspectorate Apparatus Area. The data used in this research is the primary data collected from offices of Government Inspectorate Pangkalpinang city through the spread of the questions. Population in this research is all of Government Inspectorate Pangkalpinang city as the object of research. The technique of the sample is a cencus or often called sampling saturates. A method of analysis of data in use in this research is of multiple of regression .From the results of the multiple regression analysis with significant levels of 5% obtained Independence and results in a partial motivation and significant Â positive impact on the quality of auditors in the financial control area, whereas the integrity and competence of the variable has no effect. Simultaneously the four variables that affect the quality of free Auditors in the area of financial Supervision of 97,9% it means the fourth free variables in the model has posed a considerable contribution to the quality of Auditors in the financial control area.